Staphylococcus aureus isolados de linguiças suínas e de frango do tipo frescal: perfil de suscetibilidade e caracterização molecular - Bernardo, Larissa Gomes (2015)
This study aimed to isolate and identify Staphylococcus aureus in fresh sausages that were handmade or industrially produced, and characterize isolates for susceptibility to antimicrobial agents and the presence of virulence genes. We collected 86 samples of fresh sausages, pork and chicken, in butchers of the city of Aparecida de Goiânia, Goiás. The temperature of the sausages was also measured at the time of collection. After microbiological analysis, the isolates were submitted to the antibiogram by disk diffusion technique, to typing by Pulsed Field Gel Electrophoresis and to detection of virulence genes by Polymerase Chain Reaction. Most sausages collected (68.6%) showed temperature above 4 ° C, ranging from 4.98 °C to 9.89 °C. Six samples were contaminated with Staphylococcus sp., with seven isolates, but with scores within the standard set by the Brazilian law (5.0 x 103 colony forming units per gram). Of the seven isolates obtained from different brands, collected in different butchers, three were identified as Staphylococcus aureus by detection of the femA gene, were sensitive to all antibiotics tested and showed 100% similarity by Pulsed Field. The genes encoding the hemolysins A and B, and enterotoxin H were detected in three of S. aureus strains and in one of them were already detected the genes encoding enterotoxins G and I. The survey allowed to detect S. aureus in fresh sausages, and the possibility of expression of enterotoxins genes., The presence of isolates genetically identical identified in samples obtained of distinct brands and from different butchers indicate common source of contamination or spread of particular strains in this type of food. It should be noted therefore the need to observe the product's storage conditions such as temperature when that significant amounts of toxins are not produced and become risk for the occurrence of outbreaks.